Clinical and microscopic Check for presence in Peru of American trypanosomiasis - Escomel, Edmundo (1920)
We have previously made ​​it known that Triatoma infestans exist in the valleys of southern Peru (Moquegua, Arica, Tambo, Vitor Siguas and Majes) ​​more is found that this variety of Triatoma or Chirimacha transmit disease, whereas our patient we has said that in the jungle region of their origin, Tahuamanu vinchucas are abundant and is well established that these individuals are the vectors of the disease against the learned professor would describe master Doctor Chagas.